An analysis of completeness and quality of adverse drug reaction reports at an adverse drug reaction monitoring centre in Western India - Manali Mangesh Mahajan; Urmila Mukund Thatte; Nithya Jaideep Gogtay; Siddharth Deshpande (Perspectives in Clinical Research, 2018)
Purpose/Aim: The Adverse Drug Reaction [ADR] form is the source document for the Pharmacovigilance Programme of India [PvPI] and captures information first hand from the patient. The raw data from it then gets converted into an individual case safety report [ICSR] after entry into Vigiflow. The National Coordinating Centre [NCC] uses an instrument to assess quality of these ICSRs. We carried out the present study to assess whether the same instrument with minor modifications could be used to check the quality of ADR forms at our centre. Materials and Methods: ADR reports of three months from three consecutive years were selected randomly. The ADR form [18 fields] was matched with the NCC instrument [14 fields] as the latter is made from the former. A perfect ICSR would score 1. Three fields in the NCC instrument - case narrative, compliance with standard operating procedures [SOPs] and free text [5 components] were modified, while the rest were retained. Zero was given to the first two fields. In the third field, we retained only 3/5 components and changed the last two components [sender and reporter comments] to dechallenge and rechallenge while keeping the total score the same. Results: A total of 1008 ADR reports were analyzed. We found an overall completeness score of approximately 80% with the lowest completeness score being for the year 2015. The mandatory fields had close to 100% scores. Conclusion: The NCC instrument was found well suited to evaluate quality and completeness of ADR forms.